Os tipos das plantas vasculares do herbário da Universidade Federal de Viçosa (VIC). IV - Ottonia - Nunes Vidal, Waldomiro; R Vidal, Maria Rosária (Revista Ceres, 2025)
This paper consists of a selection of types of Ottonia from the Vigosa herbarium (VIC). Transcriptions of the original descriptions were made, thereby attempting to establish the categories of the types existing in the herbarium.